Clinically Aggressive Diffuse Capillary Telangiectasia of the Brain Stem: A Clinical Radiologic-PathologicCase Study - Huddle, Daniel C.; Chaloupka, John C.; Sehgal, Vivek (American Journal of Neuroradiology, 1999)
Summary: Capillary malformations or telangiectasias of the brain usually exhibit a benign clinical course, although occassionally they may be associated with mild to moderate symptomatology of uncertain origin. We report a case of an exceptionally aggressive capillary telangiectasia in a child, which was associated with progressive neurologic deterioration resulting in death.